On d-divisible α-labelings of C4k × Pm - Pasotti, Anita (Utilitas Mathematica, 2013)
In [9] the concept of a d-divisible α-labeling has been introduced as a generalization of classical α-labelings and it has been shown how it is useful to obtain certain cyclic graph decompositions. In the present paper it is proved the existence of d-divisible α-labelings of C4k × Pm for any integers k ≥ 1, m ≥ 2 for severed values of d.